KRISHNA ESTUARINE COMPLEX WITH REFERENCE TO ITS SHRIMP AND PRAWN FISHERY - Ravindranath, K (Indian Journal of Fisheries, 2011)
The physiography of the lower reaches of river Krishna and the adjoining coast is described. Annual variation in salinity, temperature and dissolved oxygen of the coastal waters at one station is presented. A brief account of the fishing craft and gear, and a list of the 47 species of shrimps and prawns recorded from the area are given.